Is it possible to use the male calling signal analysis for species diagnostics in Dictyophara Germar, 1833 (Hemiptera: Fulgoroidea: Dictyopharidae)? - Tishechkin, Dmitri Yu. (Zootaxa, 2024)
Comparative analysis of the male calling signals of five species of Dictyophara showed that signals of different species do not differ either in oscillograms and frequency spectra or in the mean values and ranges of the pulse repetition period. D. europaea differs from four other species by the specific trend of the pulse repetition period change from the beginning to the end of signal; signals of D. pannonica, D. scolopax, D. avocetta, and D. nekkana are indistinguishable in this parameter. Thus, unlike most other Auchenorrhyncha, in Dictyophara, the male calling signal analysis cannot be used for species diagnostics. Apparently, sympatric species of this genus, in addition to the male calling signals, use some other cues for a conspecific mate recognition.